From the History of Cultural Cooperation Between the Murmansk Region and the Scandinavian Countries and Finland (1985 – 2008) - Taraskina, Olga (Nordlit, 2009)
Culture has always been one of the most neglected aspects of the critical analysis of cross-border cooperation. It is the least studied and least understood aspect of international cooperation. That's why it is clear that the study of culture and cross-border cooperation is needed now. Thesubject of this article is cultural cooperation between the Murmansk region, the Scandinavian countries and Finland. This article will examine cooperation in the field of libraries and literature studies, and cooperation in the exhibition and management of the museums within this Region.